Production localization factors: an industrial and literature based review - Bjelkemyr, Marcus; Wiktorsson, Magnus; Bruch, Jessica; Rösiö, Carin; Bellgran, Monica (Cranfield University Press, 2013)
Decision are commonly based on the available or easily accessible information; this is also true for more complex assessments like production localization. Where to locate production is often a key strategic decisions that has great impact on a company’s profitability for a long time; insufficient business intelligence may therefore have grave consequences. Six production localization factor studies have been assessed to see if they are focusing on the same issues and if there are any gaps. A new approach for structuring localization factors and the localization process is then presented and assessed with regards to some previously identified critical issues.
Keywords: production system; production localization; industrial study; localization factors